Comportamento térmico do solo de Jaboticabal, SP, sob três diferentes coberturas - Leite Vianello, Rubens; Bouhld André, Romísio Geraldo; da Silva Marques, Valdo (Revista Ceres, 2025)
The soil thermal behaviour at Jaboticabal, State of São Paulo, Brazil, was studied under conditions of bare soil, grass cover and mulching. The data utilized were collected during the period of 1972 to 1976 at 0700, 0900, 1500 and 2100 hours local time and at depths of 2, 5, 10, 20 and 30 centimeters. The theoretical analysis was based on the solution of the heat conduction equation applied to a homogeneous medium. This solution was expanded in Fourier series and the first five harmonics were computed in their amplitude and phases. The thermal diffusivity and damping depth were also computed and compared with results obtained by others researchers. All of the results were presented in tables and diagrams and an analysis was carried out for each cover condition and finally compared with itself.